EFEKTIVITAS PENDAMPINGAN FAMILY DEVELOPMENT SESSION DAN EFEKTIVITAS PENGGUNAAN MEDIA DENGAN TINGKAT PARTISIPASI KELUARGA PENERIMA MANFAAT DALAM PROGRAM KELUARGA HARAPAN - Naabigha, Tsaabitah; Noor Rakhmad, wiwid; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The Ministry of Social Affairs applies PKH assistance to recipient communities to prevent misuse of assistance for consumptive purposes. The aim of this program is to improve the standard of living and quality of human resources in the form of changes in mindset, behavior and prosperous graduation. This research aims to examine the relationship between the effectiveness of FDS assistance and media use on the level of KPM participation with Cybernetic Theory and the Knowledge-Attitude-Behavior Model which are based on quantitative analysis. Also used is probability sampling with cluster random sampling techniques via Pearson Product Moment Correlation and Simple Linear Regression. The total sample of 85 KPM will still be active until 2024, in Ngraji Village, Grobogan. The first hypothesis in this research is that there is a relationship between the effectiveness of FDS assistance (X1) and the level of KPM participation (Y), the results show that there is no linear relationship between the two variables. The essence of assistance does not work according to the initial goal, the mentor is too dominant as an information resource so it is necessary to reconsider the approach to a good relationship with respondents. The second research hypothesis examines that there is a relationship between the effectiveness of media use (X2) and the level of KPM participation (Y), the results show that there is a linear relationship. However, the effectiveness only reached 11.4%, due to the physical limitations of the module and flipchart. Therefore, it is necessary to consider increasing the physical media duplication budget. The third hypothesis is that there is a relationship between the effectiveness of FDS assistance (X1) and media use (X2) and the level of KPM participation (Y). Based on these results, no conclusion can be drawn from the third hypothesis, because the results of the two hypotheses are inversely proportional and if the first hypothesis is continued the effectiveness value is less than 1%. Thus, continuous assistance with the media is not fully implemented and still requires the respondent's determination to be actively involved in making PKH a success